Analisis Kebijakan Fiskal dalam Perspektif Ekonomi Islam; Sebuah Kajian Historis Pada Masa Umar bin Khattab - Ferry Khusnul Mubarok (Jurnal Iqtisad, 2021)
Fiscal policy in the Islamic period underwent various developments, both progress, and setbacks. Umar bin Khattab became one of the successful caliphs in the economic field, especially in managing his public finances. This article aims to identify fiscal policies in the time of the Caliph Umar bin Khattab, starting from the budget policy system, the financial management and allocation system, and its success. The method used is a qualitative approach. The data source used is secondary data with library research techniques, namely by collecting data derived from books, research results, websites, and other relevant sources. Analysis of data using descriptive technical analysis. The results of the discussion showed that fiscal policy during the Caliph Umar bin Khattab used a balanced budget system that was managed through Baitul Maal. Fiscal policy instruments developed include zakat, infaq, sedkah, wakaf, ghanimah, fa'i, kharaj, jizyah, ushur, and khums. Meanwhile, in terms of expenditure on budget allocation based on a priority scale, then it is used to fulfill the needs of mustahik, defense and security, social and religious, and state administration.